DEVELOPMENT OF JAMS FROM LOCAL RAW MATERIALS WITH A REDUCED GLYCEMIC INDEX - SERDYUK, MARINA; BANDURA, VALENTYNA; KOLISNYCHENKO, TETIANA; SEFIKHANOVA, KATERYNA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The work is devoted to the development of a recipe for jams from local raw materials with a reduced glycemic index. The main raw materials for the production of jams were apples of the Idared variety and sea buckthorn fruits of the Velikoplodna variety. Lemon mint, honey, Jerusalem artichoke, erythritol, and apple pectin were used as additional raw materials. Three recipe compositions of jams were developed for scientific research. The first stage of the study was to determine the main components of the chemical composition of the raw materials, which characterize its functional properties. The second stage was the preparation of experimental samples of jams from the specified local raw materials, determining their main indicators of chemical composition and organoleptic properties. The results of the research confirmed that the experimental samples of jams have better functional characteristics compared to the control sample. The main differences are observed in the reduced content of sugars, increased amounts of ascorbic acid and phenolic compounds, which contributes to the improvement of the antioxidant properties of the experimental jams. Particularly noteworthy is the jam made from Jerusalem artichoke syrup and erythritol, which is characterized by the lowest level of sugars and the highest content of phenolic substances and ascorbic acid. This indicates its improved biological value and ensures suitability for consumers who prefer products with a reduced glycemic index. Jam made from honey also has significant improvements in the content of functional substances, although its sugar level remains relatively high and requires caution when consumed. Jam made according to a traditional recipe, due to its stable consistency, bright color and classic taste, as well as high biological value, is a promising universal option for mass production.